PENERAPAN MODEL KOOPERATIF DENGAN METODE THINGKING ALOUND PAIR PROBLEM SOLVING (TAPPS) DALAM MENINGKATKAN KETRAMPILAN PEMECAHAN MASALAH DAN HASIL BELAJAR SISWA DALAM KONSEP SISTEM EKSKRESI KELAS VIII SMP NEGERI 1 AMBON - Jona Wisye Ririmasse; F Leiwakabessy (BIOPENDIX, 2019)
Background: Education is one of the important factors in efforts to improve human resources in Indonesia. The latest methods and methods of learning are used to streamline the conventional learning process. Cooperative learning model with TAPPS (Thinking Aloud Pair Problem Solving) method in improving problem solving skills and student learning outcomes in the concept of class VIII excretion system at SMPN 1 Ambon. Method: This study is a descriptive study that is by giving treatment in the form of learning by using cooperative learning models with the TAPPS method for class VIII students of SMP 1 Ambon, amounting to 21 people. Results: In the cognitive, affective, and psychomotor aspects all students are said to be complete, with an average value of each aspect namely for cognitive 86.1 for affective 84.43 and psychomotor 83.1. While for problem solving skills obtained an average of 86.1. From the average value obtained by students, cooperative learning models with the TAPPS (Thinking Aloud Pair Problem Solving) method can improve problem solving skills and student learning outcomes. Conclusion: The application of the cooperative learning model with the TAPPS (thinking aloud pair problem solving) method to increasing the results of learning excretion system concepts in class VIII2 of SMPN 1 Ambon showed a significant success rate